Heteroleptic Tin(II) Initiators for the Ring‐Opening (Co)Polymerization of Lactide and Trimethylene Carbonate: Mechanistic Insights from Experiments and Computations. Issue 40 (19th August 2013) - Wang, Lingfang; Kefalidis, Christos E.; Sinbandhit, Sourisak; Dorcet, Vincent; Carpentier, Jean‐François; Maron, Laurent; Sarazin, Yann
Abstract The tin(II) complexes LOxSn(X) (LOx−=aminophenolate ancillary) containing amido (1–4), chloro (5), or lactyl (6) coligands (X) promote the ring‐opening polymerization (ROP) of cyclic esters. Complex 6, which models the first insertion of L‐lactide, initiates the living ROP of L‐LA on its own, but the amido derivatives 1–4 require the addition of alcohol to do so. Upon addition of one to ten equivalents of iPrOH, precatalysts 1–4 promote the ROP of trimethylene carbonate (TMC); yet, hardly any activity is observed if tert‐butyl (R)‐lactate is used instead of iPrOH. Strong inhibition of the reactivity of TMC is also detected for the simultaneous copolymerization of L‐LA and TMC, or for the block copolymerization of TMC after that of L‐LA. Experimental and computational data for the LOxSn(OR) complexes (OR=lactyl or lactidyl) replicating the active species during the tin(II)‐mediated ROP of L‐LA demonstrate that the formation of a five‐membered chelate is largely favored over that of an eight‐membered one, and that it constitutes the resting state of the catalyst during this (co)polymerization. Comprehensive DFT calculations show that, out of the four possible monomer insertion sequences during simultaneous copolymerization of L‐LA and TMC: 1) TMC then TMC, 2) TMC then L‐LA, 3) L‐LA then L‐LA, and 4) L‐LA then TMC, the first three are possible. By contrast, insertion of L‐LA followed by that of TMC (i.e., insertion sequence 4) is endothermic by +1.1 kcal mol−1, which compares unfavorably with consecutive insertions of two L‐LA units (i.e., insertion sequence 3) (−10.2 kcal mol−1). The copolymerization of L‐LA and TMC thus proceeds under thermodynamic control.